Tension space analysis: exploring community requirements for networked urban screens - North, Steve; Schnädelbach, Holger; Fatah gen Schieck, Ava; Motta, Wallis; Ye, Lei; Behrens, Moritz; Kostopoulou, Efstathia (Springer, 2013)
This paper draws on the design process, implementation and early evaluation results of an urban screens network to highlight the tensions that emerge at the boundary between the technical and social aspects of design. While public interactive screens in urban spaces are widely researched, the newly emerging networks of such screens present fresh challenges. Researchers wishing to be led by a diverse user community may find that the priorities of some users, directly oppose the wishes of others. Previous literature suggests such tensions can be handled by ‘goal balancing’, where all requirements are reduced down to one set of essential, implementable attributes. Contrasting this, this paper's contribution is ‘Tension Space Analysis’, which broadens and ex-tends existing work on Design Tensions. It includes new domains, new representational methods and offers a view on how to best reflect conflicting community requirements in some aspects or features of the design.